El Salvador : Statistical Annex. (IMF Staff Country Reports; Country Report, 2000)
The paper presents statistical data on national income accounts, components of aggregate demand, financing of investment, gross domestic product by sector, electricity indicators, consumer price indices, daily wages, population and employment, central government, distribution of public sector bonded debt, and operations of the financial system of El Salvador. It also includes data on legal reserve requirements, liquidity at the commercial banks, balance of payments, merchandise exports and imports, public external debt and debt service by creditor, effective exchange rates, and other related economic indices.